The nature and function of utopianism in the Communist Party of South Africa, 1921-1950 - Meny-Gibert, Sarah (My University, 2008)
Abstract The following study is concerned with the nature of utopianism in the Communist Party of South Africa (CPSA). The presence of utopianism is explored over the whole of the Party’s history from 1921 to 1950. The study is essentially a historical sociology piece, and is based on the assumption that ideas are constitutive of social reality, and in particular, that utopianism is an active ingredient in society. The CPSA’s utopian vision for a future South African emerged amidst the excitement generated amongst socialists worldwide by the success of the Bolshevik Revolution. Over the years CPSA members drew on a range of traditions and identities that shaped the content and form of the CPSA’s utopianism. This utopianism was influenced by a modernist discourse of Marxism, which was characterised by a strong confidence in the realisation of a socialist future. The CPSA’s vision was also shaped by the political landscape of South Africa, and by the influence of the Communist International. The discussions of the CPSA’s form and content provide background to an analysis of the function of utopianism in the CPSA. An investigation of utopianism’s function in the Party informs the most significant finding of the research. Utopianism played a positive role in the CPSA: it was a critical tool, and a mobilising and sustaining force. However, utopianism in the CPSA also revealed a destructive side. The negative role of utopianism in the CPSA is explored via two themes: the ‘Bolshevisation’ or purging of the CPSA in the 1930s under the directive of the Communist International, and the CPSA’s often blind loyalty to the Soviet Union. The presence of utopianism in the CPSA is thus shown to have been ambiguous. In conclusion it is suggested that utopianism is an ambiguous presence in society more generally, as it has the potential to function as both a positive and a negative force in society. This is an under explored topic in the literature on utopianism. The role that utopianism will play in any given social group is context related, however. The study argues for a more contextualised approach than is adopted in many of the seminal texts on utopia, to understanding the way in which utopianism is manifest and functions in society. The study sheds new light on the history of the Party, by revealing a previously unexplored story in the CPSA’s history, and makes a contribution to sociology in providing a detailed exploration of the nature and function of utopianism.
Keywords: CPSA; Communist Party of South Africa; Utopia; utopianism; South African Communist Party; SACP